2008
DOI: 10.1007/s00404-008-0630-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of macrosomia on the duration of labor, the mode of delivery and intrapartum complications

Abstract: As some of the risk factors identified are known prior to delivery, every woman in whom there is a suspicion that the fetus may weigh up to 4,500 g should receive individual guidance regarding special intrapartum and perinatal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 17 publications
8
37
0
Order By: Relevance
“…Women delivering macrosomic infants more often experiences a number of adverse birth outcome (109-112) and prolonged labor (110). Prolonged second stage of labor may increase the risk of postpartum hemorrhage (113), the incidence of acute cesarean section (114) or vaginal operative delivery (111). Delivering of a macrosomic fetus also increases the risk of third or fourth degree lacerations (110).…”
Section: Maternal Health Consequences Short Term Risksmentioning
confidence: 99%
“…Women delivering macrosomic infants more often experiences a number of adverse birth outcome (109-112) and prolonged labor (110). Prolonged second stage of labor may increase the risk of postpartum hemorrhage (113), the incidence of acute cesarean section (114) or vaginal operative delivery (111). Delivering of a macrosomic fetus also increases the risk of third or fourth degree lacerations (110).…”
Section: Maternal Health Consequences Short Term Risksmentioning
confidence: 99%
“…A high ratio indicates a large placental weigh relative to birth weight. All singleton pregnancies in Norway from 1999 through 2004 (n = 308 717) [3][4][5]8,15 We also found a positive association of high birthweight, but after adjustment for placental weight, the association of birthweight was strongly attenuated. It has been suggested that impaired uterine contractions may occur more often after deliveries of large babies, and one consequence of this could be a longstanding postpartum haemorrhage.…”
Section: Discussionmentioning
confidence: 79%
“…3,[6][7][8][9][10] A large placenta will typically have a large surface area attached to the uterine wall, and it is therefore conceivable that large placental size is associated with increased risk of excess postpartum haemorrhage. Such an association may partly explain why women who deliver large babies are at higher risk of postpartum haemorrhage 5 because birthweight and placental weight are strongly correlated. 11 We hypothesised that placental weight is positively associated with excess postpartum haemorrhage also after adjustment for offspring birth size and other risk factors of excess postpartum haemorrhage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive invasion by EVT can also be detrimental in cases such as placenta accreta. High birth weight is potentially dangerous to both mother and baby through prolonged obstructed labour [5,6] with risk of asphyxia and injury in the baby [7][8][9], and lacerations and post-partum haemorrhage in the mother [5,9]. It is therefore crucially important that this process is carefully regulated maintaining a balance between over and under invasion.…”
mentioning
confidence: 99%